Oil-based nanoemulsion of Metarhizium anisopliae (Metschn) sorokin to control red palm weevil Rhynchophorus ferrugineus (Olivier) - Abdulqader, Ali Zachi (2018)
Oil based emulsion formulations of Metarhizium anisopliae were prepared, characterised and evaluated for their effectiveness against the larvae and adults of Rhynchophorus ferrugineus. Infested R. ferrugineus adults were collected from Terengganu,andM. anisopliae was isolated by cadavers of red palm weevil adults. Four strains were obtained and identified via morphology and molecular technique as M. anisopliae. The virulence of these strains was evaluated against the adult and larvae of R. ferrugineus by time exposure mortality bioassay. The strain coded as D1 gave the lowest LT50 values of 7.2 and 5.2 days at the conidia concentration of 106 and 107 spores/mL, respectively against the larvae. While against the adult, the D1 strain also gave the lowest LT50 values of 6 and 5 days at same conidia concentrations. Oil emulsion formulations of the most virulence isolate conidia of M. anisopliae were prepared through ternary phase diagram consisting of 20% (w/w) surfactant, 40% (w/w) oil and 40% (w/w) water containing 107spore/mL. The surfactants and oil were first evaluated for their compatibility with conidia by using direct plating. The effect of the surfactants on conidia germination was evaluatedby counting the germination rate of the conidia using a microscope. Agnique PG9116 at 1% concentration gave 87.5 % germination while at 5% surfactant Emereen1604 and EW70 gave 70% conidia germination. In a study of the effect of oils on the conidia germination, glycerin oil gave highest conidia germination rate. Sunflower and glycerin showed less inhibition at 1% concentration with 49.13 and 44.13% growth rate respectively.Palm oil at 5% concentration was the best with 56.88% growth rate. At 10% concentration of oils, soybean and glycerin gave 48.63 and 45.38% growth rate respectively. Eight ternary phase diagram systems were then constructed. The selected systems showed large isotropic regions. They were Agnique PG9116/ glycerin/ water, Emereen1604/ glycerin/ water, Tensiofix 96 DB08/ glycerin/ water, Tensiofix 96 DB10/ glycerin/ water, Tensiofix EW 70/ glycerin/ water, Termul 1284/ glycerin/ water, Tween20/ glycerin/ water and Tween80/ glycerin/ water. Eight oil emulsion formulations were derived and characterised. All the formulations were stable under centrifuge, storage at 26 ± 1 °C, 60 ± 5 % RH and under high temperature (54± 1 °C) for two weeks. On the particle size, seven formulations were in the range below ˂100 nm sizes indicating that the formulations were in the category of the nanoemulsion. The zeta potential of the formulations ranged between -7.22 to -39.06 mV, the pH ranged from 4 to 6.34, the surface tension ranged from 32.03 to 41.83 mN/m, and the viscosity ranged from 2.40 to 28.8 mPas. In the study on the toxicity of the oil nanoemulsion formulations of M. anisopliae conidia against the larvae, the formulation coded as E1604 gave the LT50 of 4.90 days while the conidia water suspension gave LT50 of 6 days. On adults, the LT50 was 2.20 days while the conidia water suspension was 5 days. Effect of oil nanoformulations on the conidia germination on the cuticle of R. ferrugineus was also observed, and after 20 hrs., the E1604 showed 55% germination compared to conidia water suspension of 49.8%. The formulation E1604 showed the longest germ tube of 41.34 μm and full penetration while the conidia water suspension gave 5.28 μm length of a germ tube. The E1604 recorded 100% cumulative mortality after 6 and 4 days on larvae and adults respectively. The oil nanoemulsion of M. anisopliae conidia shows good potential for the sustainable control of both adults and larvae of R. ferrugineus.